Correlation between Reduced FEF25-75% and a Positive Methacholine Challenge Test in Adults with Nonobstructive Baseline Spirometry. (29th December 2021) - Shafiq, Irfan; Uzbeck, Mateen Haider; Zoumot, Zaid; Abuzakouk, Mohamed; Parappurath, Niyas; Wahla, Ali Saeed
Abstract : Rationale . FEF25-75% is routinely reported on spirometry and is thought to be a marker of small airway obstruction. It is reduced in children with asthma, but its significance in adults and especially those without asthma diagnosis remains unclear. Objective . To clarify whether in adults with a nonobstructive spirometry a reduced FEF25-75% is associated with a positive methacholine challenge test (MCT). Methods . Data was collected for all the patients who had a MCT done between April 2014 and January 2020 but had nonobstructive baseline spirometry. Logistic regression was utilized to estimate the log odds of a positive methacholine test as a function of FEF25-75% and also for age, gender, BMI, FEV1, and FEV1/FVC. Results . Out of 496 patients, 187 (38%) had a positive MCT. Baseline characteristics in two groups were similar except that patients with positive MCT were younger (32 ± 11.57 vs. 38 ± 13.25 years, respectively, p < 0.001 ). Mean FEF25-75% was lower in MCT positive (3.12 ± 0.99  L/s) vs. MCT negative (3.39 ± 0.97  L/s) patients, p = 0.003 . Logistic regression results suggest that MCT outcome is inversely related to FEF25-75%, age, and gender. Specifically, as FEF25-75% percentage of predicted value increases, the log odds of a positive MCT decrease (odds   ratio   OR = 0.90, 95% confidence intervals   CI = 0.84 ‐ 0.96, p = 0.002 ). Also, as age increases, the log odds of a positive MCT decrease (OR = 0.95, 95 % CI = 0.94 ‐ 0.97, p < 0.001 ). Conclusions . Reduced FEF25-75% in adults with nonobstructive spirometry can predict a positive response to MCT in younger patients. However, this relationship becomes weaker with increasing age.